2016
DOI: 10.1111/cpr.12230
|View full text |Cite
|
Sign up to set email alerts
|

miRNA‐30e regulates abnormal differentiation of small intestinal epithelial cells in diabetic mice by downregulating Dll4 expression

Abstract: Increased levels of miRNA-30e downregulated activity of the Dll4/NICD/Hes1 signalling pathway by targeting the 3'-UTR of Dll4, which contributed to abnormal differentiation in small intestinal epithelia of DM mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 43 publications
2
35
0
Order By: Relevance
“…MicroRNAs (miRNAs) are a group of small, nonprotein coding, endogenous and single-stranded RNAs that negatively regulate target mRNA to either translational or mRNA degradation (7)(8)(9)(10)(11)(12). Emerging evidence has shown that miRNAs play pivotal roles in cellular functions, such as apoptosis, proliferation, motility and differentiation (13)(14)(15)(16)(17). Aberrant miRNA expression is found in various cancers including gastric, breast cancer, glioma, hepatocellular carcinoma, ovarian carcinoma, osteosarcoma and PDAC (7,(18)(19)(20)(21)(22)(23).…”
Section: Introductionmentioning
confidence: 99%
“…MicroRNAs (miRNAs) are a group of small, nonprotein coding, endogenous and single-stranded RNAs that negatively regulate target mRNA to either translational or mRNA degradation (7)(8)(9)(10)(11)(12). Emerging evidence has shown that miRNAs play pivotal roles in cellular functions, such as apoptosis, proliferation, motility and differentiation (13)(14)(15)(16)(17). Aberrant miRNA expression is found in various cancers including gastric, breast cancer, glioma, hepatocellular carcinoma, ovarian carcinoma, osteosarcoma and PDAC (7,(18)(19)(20)(21)(22)(23).…”
Section: Introductionmentioning
confidence: 99%
“…The Notch signaling pathway is a highly conserved signaling mechanism in many processes determining cell fate during development in the adult organism . Activation of Notch occurs following Notch receptor/ligand engagement, which initiates translocation of the Notch intracellular domain to the nucleus and activation of target genes .…”
Section: Resultsmentioning
confidence: 99%
“…When we looked at potential target molecules for miR-30, we found through in silico analyses that it may target the 3’UTR of Dll4 ( Supplemental Figures 2A–2C ) Previous studies had confirmed miR-30- Dll4 targeting using luciferase reporter assay 30 , 31 . Interestingly, DLL4 has been shown to be involved in Notch signaling 9 , 32 , 33 .…”
Section: Resultsmentioning
confidence: 99%